BEFORE AND AFTER COMPARISON STUDY ON SINGLE-USE PLASTIC BAN IMPLEMENTATION AMONG URBAN COMMUNITY RESIDENTS IN PUDUCHERRY, SOUTH INDIA - Kittu, Devi; Chellamuthu, Lalithambigai; Sivapushani, Aruljothi (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objective: Plastic industry is rapidly growing industries in India. To assess the knowledge, attitude, and practice of plastic usage before and after plastic ban in urban Puducherry. Methods: A community-based, non-randomized control trial (before and after comparison study) was conducted from May to October 2019 (6 months) at an urban field practice area of a Government Medical College in Puducherry. The study population were community residents aged above 18 years from the selected wards of urban field practice areas. The systematic random sampling was employed to cover 450 community residents. Data were collected by face-to-face interview into a pre-tested, semi-structured questionnaire. The pre-ban data collection was completed in July 2019. Ban on single-use plastics was implemented in Puducherry by August 1, 2019. After 1 month of ban (wash-out period), post-ban data collection was done among the same residents during September 2019. Data were captured using epi-collect and analyzed using the SPSS 16. Ethical clearance was obtained from the Institutional Ethics Committee. Results: Mean age of study participants was 39.64 (13.23) years, of which 255 (56.7%) of them were females. The median income of the respondents was 16000 (25000). Before ban 403 (89.6%) were carrying their shopping items or products using plastic bags provided by the shopkeeper whereas post-ban, it has reduced to 102 (22.7%). Mean KAP (knowledge, attitude, and practice) scores before ban was 9±3.8 (95% CI 6.6–9.2), and after ban, mean scores increased to 17.2±1.5 (95% CI 16.2–18.4). A pair t-test was done between the pre- and post- ban KAP scores and was found to be statistically significant (p=0.000). Conclusion: Most participants were aware of both environmental and health hazards from plastics and supported the single-use plastics ban.